2014
DOI: 10.1016/j.humimm.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Frequency analysis of HLA class I alleles in Iranian patients with progressive and non-progressive chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is a malignant disorder of B cell origin, with low incidence in Asian populations. In this study we investigated the HLA-class I A and B allele frequencies in 87 Iranian CLL patients and 64 healthy controls using sequence specific primer-polymerase chain reaction (SSP-PCR) technique. Our results showed increased frequencies of HLA-A11:01 (p=0.02) and HLA-B35:01 (p=0.002) alleles and HLA-A11:01/B35:01 haplotype (p=0.036) and decreased frequencies of HLA-A01:01 (p=0.02), HLA-A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Among other race/ethnic populations, increased CLL risk associations among Iranians have been reported for HLA‐A*11:01 (OR = 3.38, 95% CI = 1.16–10.55) and HLA‐B*35:01 (OR = 3.51, 95% CI = 1.48–8.6) and their combined haplotype ( P ‐value = 0.036), HLA‐DRB1*07 (OR = 2.19, 95% CI = 1.02–4.75), DQB1*06 (OR = 1.19, 95% CI = 1.13–3.2) and DRB1*13˜DQB1*03 haplotype (OR = 4.29, 95% CI = 1.29–15.75) . In the same population, decreased CLL risk was reported for HLA‐A*01:01 (OR = 0.34, 95% CI = 0.13–0.87), HLA‐A*26:01 (OR = 0.32, 95% CI = 0.10–0.92), HLA‐B*65:01 (OR = 0.17, 95% CI = 0.03–0.91), HLA‐B*53:01 (OR = 0.04, 95% CI = 0.01–0.32) and HLA‐DQB1*03 (OR = 0.58, 95% CI = 0.36–0.91).…”
Section: Chronic Lymphocytic Leukaemia/small Lymphocytic Lymphomamentioning
confidence: 99%
“…Among other race/ethnic populations, increased CLL risk associations among Iranians have been reported for HLA‐A*11:01 (OR = 3.38, 95% CI = 1.16–10.55) and HLA‐B*35:01 (OR = 3.51, 95% CI = 1.48–8.6) and their combined haplotype ( P ‐value = 0.036), HLA‐DRB1*07 (OR = 2.19, 95% CI = 1.02–4.75), DQB1*06 (OR = 1.19, 95% CI = 1.13–3.2) and DRB1*13˜DQB1*03 haplotype (OR = 4.29, 95% CI = 1.29–15.75) . In the same population, decreased CLL risk was reported for HLA‐A*01:01 (OR = 0.34, 95% CI = 0.13–0.87), HLA‐A*26:01 (OR = 0.32, 95% CI = 0.10–0.92), HLA‐B*65:01 (OR = 0.17, 95% CI = 0.03–0.91), HLA‐B*53:01 (OR = 0.04, 95% CI = 0.01–0.32) and HLA‐DQB1*03 (OR = 0.58, 95% CI = 0.36–0.91).…”
Section: Chronic Lymphocytic Leukaemia/small Lymphocytic Lymphomamentioning
confidence: 99%
“…There are several studies of the distributions of HLA alleles in diverse populations with CLL. For example, studies of Iranians with CLL reported increased frequencies of A*11:01, B*35:01, DRB1*07 and DRB1*06 are increased whereas A*01:01, A*26:01, B*65:01, B*53:01 and DRB1*03 are decreased [47,48]. Data from a large study of persons of predominately European descent with CLL reported a high degree of linkage disequilibrium between certain HLA alleles and HLA-haplotypes [49].…”
Section: Hla Associationsmentioning
confidence: 99%
“…Basaran et al [ 59 ] highlight the protective role of HLA-B35 against neoplastic transformation in patients with mycosis fungoides and Sézary syndrome. On the other hand, Hojjat-Farsangi et al [ 60 ] report a higher incidence of HLA-B*35:01 in patients with chronic lymphocytic leukemia. Also, Brazzelli et al [ 39 ] noticed an association between HLA-B*35 and mycosis fungoides.…”
Section: Discussionmentioning
confidence: 99%